2022
DOI: 10.1186/s41065-022-00222-3
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine-related lncRNAs is a potential marker for predicting prognosis and immunotherapy in ovarian cancer

Abstract: Background With a lack of specific symptoms, ovarian cancer (OV) is often diagnosed at an advanced stage. This coupled with inadequate prognostic indicators and treatments with limited therapeutic effect make OV the deadliest type of gynecological tumor. Recent research indicates that N6-methyladenosine (m6A) and long-chain non-coding RNA (lncRNA) play important roles in the prognosis of OV and the efficacy of immunotherapy. Results Using the Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Using the OC-related dataset from The Cancer Genome Atlas (TCGA), Nie et al confirmed the prognostic potential of 21 m 6 A modifications in OC and identified two m 6 A subtypes using the m 6 A-related gene expression profiles [ 93 ]. Then, the authors established an OC risk model based on the differential expression pattern of lncRNAs between the m 6 A subtypes and lncRNAs co-expressed with the m 6 A-related genes [ 93 ]. The risk model not only simply evaluated the predictability of tumor prognosis using the risk score but also assessed the effectiveness of immunotherapy and developed novel and more accurate immunotherapies.…”
Section: A and Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the OC-related dataset from The Cancer Genome Atlas (TCGA), Nie et al confirmed the prognostic potential of 21 m 6 A modifications in OC and identified two m 6 A subtypes using the m 6 A-related gene expression profiles [ 93 ]. Then, the authors established an OC risk model based on the differential expression pattern of lncRNAs between the m 6 A subtypes and lncRNAs co-expressed with the m 6 A-related genes [ 93 ]. The risk model not only simply evaluated the predictability of tumor prognosis using the risk score but also assessed the effectiveness of immunotherapy and developed novel and more accurate immunotherapies.…”
Section: A and Ocmentioning
confidence: 99%
“…LncRNAs are a group of 200-nucleotides long RNA, which regulate gene expression and various physiological and pathological processes [91,92]. Using the OC-related dataset from The Cancer Genome Atlas (TCGA), Nie et al confirmed the prognostic potential of 21 m 6 A modifications in OC and identified two m 6 A subtypes using the m 6 A-related gene expression profiles [93]. Then, the authors established an OC risk model based on the differential expression pattern of lncRNAs between the m 6 A subtypes and lncRNAs co-expressed with the m 6 A-related genes [93].…”
Section: Prognostic Effect Of M6a In Ocmentioning
confidence: 99%
“…In addition, other potential markers, including circulating tumor DNA (ctDNA) [6], microRNAs (miRNAs) [7], and long non-coding RNAs (lncRNAs) [8], have been extensively studied in recent years and provide potential new methods for early diagnosis and prognosis. Research on lncRNA-based prognostic markers for OV has led to the development of prognostic models, including immune [9], autophagy [10], and N6methyladenosine-related lncRNA prognostic models [11]. We are currently investigating a new method to improve prognosis of patients with OV.…”
Section: Introductionmentioning
confidence: 99%